Reviewers Acknowledgements - jamel Eddine HENCHIRI (Academic Finance, 2023)
Journal of Academic Finance wishes to acknowledge the following individuals for their assistance with peer review of manuscripts for this issue. We greatly appreciate their help and contributions maintaining the quality of the journal.